Nano-textured surfaces using hybrid micro- and nano-materials for efficient water cooling. (August 2018) - Kim, Min-Woo; Kim, Tae Gun; Jo, Hong Seok; Lee, Jong-Gun; James, Scott C.; Choi, Mun Seok; Kim, Woo Yeong; Yang, Jae Sin; Choi, Jeehoon; Yoon, Sam S.
Highlights: Water cooling heat transfer was enhanced by texturing the heated surface with various micro- and nano-materials. The increased surface area enhanced convection and turbulent mixing. A substrate was textured with electroplated copper oxide, sprayed silver nanowire or sprayed copper micro-particles. The texturing methods are appropriate for electronics cooling applications because of their simplicity and scalability. Abstract: Water cooling heat transfer was enhanced by texturing the heated surface with various micro- and nano-materials. The increased surface area by texturing facilitated not only enhanced convection, but also turbulent mixing, which increased the effective heat-transfer coefficient. A heated copper substrate was textured with electroplated copper oxide, sprayed silver nanowire, or sprayed copper micro-particles. Sprayed micro-particles were subsequently nano-textured by sand blasting with kanthal (Mo2 Si) nanoparticles. Because of the extremely high hardness of kanthal, sand blasting dimpled the surface to increase the total surface area. Optimal texturing was identified for each material. Hybrid cases combining two different texturing materials were also investigated. All cases were quantitatively compared and that with the highest effective heat transfer was identified. Texturing materials were characterized by scanning electron microscopy and X-ray diffraction. The coating methods are simple, rapid, and scalable and may be cost-effective texturing schemes for various electronics cooling applications.